Enhancing the role of human resource management in corporate sustainability and social responsibility: A multi-stakeholder, multidimensional approach to HRM - Stahl, Günter K.; Brewster, Chris J.; Collings, David G.; Hajro, Aida (Human resource management review, 2020)
This paper focuses on the increased pressure for corporations to engage in corporate sustainability (CS) and corporate social responsibility (CSR) in order to address the current crisis of confidence in business, align their activities with the needs and expectations of a broader set of stakeholders, and help tackle the world's grand challenges. We argue that human resource management (HRM) has a potentially vital role to play in contributing to a firm's CS/CSR efforts, but so far has failed to deliver. We explore the reasons for this failure and discuss ways for HRM to play a more prominent role in the design and implementation of a firm's CS/CSR strategy. Building on earlier attempts to integrate corporate responsibility and sustainability into the HRM performance construct, we propose a multidimensional, multi-stakeholder approach to sustainable HRM that encompasses activities aimed both at avoiding harmful consequences for stakeholders and contributing to positive outcomes along the triple bottom line (i.e., people, planet, and prosperity). We discuss implications for research and develop a set of propositions and guidelines for future research. •We contend that HRM practitioners are not currently accepted as partners in influencing corporate sustainability and CSR strategies•The article explains the reasons for the failure of the HRM profession to take a more strategic role in organizations' sustainability and CSR strategies•We argue that if we are to make HRM research relevant we must adopt a multi-stakeholder perspective on HRM•We offer a framework of sustainable HRM performance that encompasses the three dimensions of the ‘triple bottom line’